2013
DOI: 10.3126/njst.v13i2.7713
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pesticide Residues in Some Vegetables Grown in Kavrepalanchok and Bhaktapur Districts

Abstract: Pesticides have wide spread use and their toxic residues have been reported in various environmental matrices. Thus, the determination of pesticide residues in food commodities such as vegetables, cereals, fruits, and other environmental components like soil, water has become increasingly essential requirement for consumers, producers and authorities for food quality control. Therefore, monitoring of residue level and exposure assessment of organophosphate group of pesticides namely dichlorovos and methyl para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A separate study [32] reported that residues of two commonly used active ingredients (dichlorvos and methyl parathion) exceeded the maximum residue limit (MRL) in 5 out of 33 vegetables evaluated. Further, estimated average daily intake exceeded the acceptable daily intake in~54% vegetables tested for dichlorvos and~30% vegetables tested for methyl parathion [32], both chemicals are highly toxic and banned to use in agriculture in many countries.…”
Section: Pesticide Use Pattern and Safety Practices To Prevent Pesticmentioning
confidence: 99%
“…A separate study [32] reported that residues of two commonly used active ingredients (dichlorvos and methyl parathion) exceeded the maximum residue limit (MRL) in 5 out of 33 vegetables evaluated. Further, estimated average daily intake exceeded the acceptable daily intake in~54% vegetables tested for dichlorvos and~30% vegetables tested for methyl parathion [32], both chemicals are highly toxic and banned to use in agriculture in many countries.…”
Section: Pesticide Use Pattern and Safety Practices To Prevent Pesticmentioning
confidence: 99%
“…Koirala et al, [29] reported highest level of contamination in root vegetables followed by leafy vegetables. Rawal et al, [30] also reported that estimated average daily intake (EADI) of dichlorovos exceeded the acceptable daily intake (ADI) in 18 vegetables. Residues analysis of 75 samples of 13 vegetables carried out by Sharma, (2015) reported that 4% of the total samples were reported to have above maximum residue limit (MRL).…”
Section: Pesticide Application and Residue In Food Cropsmentioning
confidence: 99%
“…Active ingredient cowpea and similarly Carbandazim and Mancozeb concentration were highest in tomato followed by bottle guard and chilli. More than 50% of the tea samples from Jhapa were found to be contaminated with different pesticides where even a banned pesticide named Ethion was reported [30].…”
Section: Cereals Fruits Active Ingredient (Kg/ha) Applied Vegetable Cmentioning
confidence: 99%
“…Vegetable farming is the major source of farm income in the district (Brown and Kennedy, 2005;Dahal et al, 2009). In the district, prior studies have informed us of the excessive use of chemical pesticides in vegetables (Atreya, 2008a(Atreya, , 2008b; and pesticide residues in (i) vegetables (Rawal et al, 2012) and (ii) soil and river water samples (Dahal et al, 2007; Kafle et al, 2015) -henceforth the potential risk for chronic health conditions because of pesticide exposure could be high for farmers who have been living and applying chemical pesticides in the area for a long period. We picked two former village development committees (VDCs) of the district: (i) Mahadevsthan -with a long history of pesticide use, high rates of pesticide application, and highly intensified farming ('case' village); and (ii) Nayagaun -where the use of pesticides was comparatively less ('control' village) [for additional details on the agricultural intensification in the study area, refer to Dahal et al (2009)].…”
Section: Study Areamentioning
confidence: 99%